The Role of Innovations in Economic Development - Shahinyan, Tatevik Vazgen (ՀՀ ԳԱԱ ՏԻ)
It is no secret that ensuring stable economic growth is one of the priorities of any country, and nowadays, innovation has a great impact on economic growth rates. Various problems that haunt society and the economy are solved through the creation and implementation of new technologies. The study of the pace of innovative development and competitiveness of countries is especially relevant. Не секрет, что обеспечение стабильного экономического роста является одним из приоритетов любой страны, и в наше время инновации оказывают большое влияние на темпы экономического роста. Посредством создания и внедрения новых технологий решаются различные проблемы, стоящие перед обществом и экономикой. Գաղտնիք չէ, որ ցանկացած երկրի առաջնահերթություններից է կայուն տնտեսական աճի ապահովումը, իսկ արդի ժամանակներում տնտեսական աճի տեմպերի վրա իրենց մեծ ազդեցությունն են ունենում նորարարությունները։ Նոր տեխնոլոգիաների ստեղծման ու ներդրման միջոցով են լուծվում հասարակության ու տնտեսության առջև ծառացած տարաբնույթ խնդիրներ։
Keywords: Macroeconomic Problems; Finance